Fonds of agricultural cooperatives in Međimurje and Koprivnička Podravina after 1945 - Požgan, Jasna (Moderna arhivistika, 2019)
The article deals with issues of agricultural cooperatives in the regions of Međimurje and Koprivnička Podravina between 1945 and 1953, and their reorganisation. The reorganisation itself had a large impact on creation of the archival collection of the agricultural cooperatives. Agricultural cooperatives were established in 1945 and in the 1950s and were active through the 1960s when they were abolished. Their records were acquired by the State Archives in Varaždin during the 1960s and 1970s. While about 30archival fonds of agricultural cooperatives are preserved in the State Archives for Međimurje, only a few are preserved in the State Archives in Varaždin, Collective Center Koprivnica. The importance of such fonds lies in the fact that records provide information about agricultural production in a certain territory and information about its management.
Keywords: agriculture; archival collection; archives; arhiv; arhivski fond; collectivisation; cooperative; kmetijstvo; kolektivizacija; zadruga